Effect of yerba mate (Ilex paraguariensis) in lamb diets on fatty acid profile, physical and sensory characteristics of the Longissimus muscle - Pena-Bermudez, Yuli A.; Lobo, Richard Roberto; de Amorim, Tamyres Rodrigues; Rojas-Moreno, Danny A.; Rodriguez-Aguilar, Daniel; Poleti, Mirele Daiana; Pereira, Angélica Simone Cravo; Pinheiro, Rafael Silvio Bonilha [UNESP]; Claudio da silva Bueno, Ives (Elsevier, 2022)
This experiment studied the effects of yerba mate extract (YME) on lamb feed as a natural antioxidant in the fatty acid profile, physical and sensory traits of the meat of 36 lambs fed for 53 days. The treatments followed the randomized block design, with a control group without YME (0%) and three groups with 1, 2, and 4% of YME inclusion in the dry matter (DM). The inclusion of YME did not significantly affect the quality and sensory characteristics of the meat. However, it has improved the value of b* (p = 0.01) for the treatment with 4% YME, as well as the branched-chain fatty acids (BCFA), exhibited a diet effect (p = 0.01) for the same group. The addition of 4% of YME improves the composition and general acceptance of lamb meat, recommended to use it in animal feed.
Keywords: Antioxidant; Human health; Lamb; Polyunsaturated fatty acids; Sensorial attributes